Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan Pada Shopee Express Mpunda Kota Bima - Wiwin Sulastri; Jaenab Jaenab; Ikbal Irawan (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the effect of workload and compensation on employee performance at Shopee Express Munda, Bima City. The research instrument used in this research was a Liker scale questionnaire. The population used in this research was all Shopee Express employees in Bima City, 56 respondents and a sample of 56 people. The sampling technique was carried out using the saturated sampling method. The data in this research was collected by observation, interviews, questionnaires and literature study. Then the data obtained was analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests. With the help of SPSS version 26. The results of the research show that 1) Workload does not have a significant effect on employee performance at Shopee Express Mpunda, Bima City, 2) Compensation has a significant effect on employee performance at Shopee Express Mpunda, Bima City. 3) Workload and Compensation have a significant effect on Employee Performance at Shopee Express Mpunda Bima City.